ENVIRONMENT EFFECTS ON DAILY MILK YIELD AND FAT AND PROTEIN PERCENTAGES OF HOLSTEIN COWS IN THE STATE OF PARANÁ - BAJALUK, Sérgio Antonio Bogdano (Scientia Agraria, 2000)
For evaluating the importance of some environmental effects on the daily milk yield and fat and protein percentages of Holstein cows in the Paraná state, 993,839 records of the data set from the Holstein Association of Paraná State were analyzed. From those records, after the application of restrictions to the data set, remained 672,881 observations, coming of 78,231 lactation set between January of 1993 and December of 1998, of 41,511 Holstein cows, belonging to 377 herds of the Paraná State. Means, standard deviations and the coefficients of variation of the daily milk yield were respectively 25.062 kg/milk/day, 8.148 and 32.511%; of the fat percentage 3.409%, 0.665 and 19.507% and of the protein percentage 3.131%, 0.335 and 10.699%. With the use of the Least Squares Method, the following environmental effects were analyzed on the mentioned characteristics: year of calving, calving season, milking frequency, stage of lactation, somatic cells count score, interaction of age and calving order, sample age and cow. All the studied effects affected significantly (P<0.01) the three studied productive characteristics, except calving year on the fat percentage, with P<0.05. Coefficients of determination (R2) and coefficients of variation(%) of the used models were 0.785 and 16.019 respectively for the daily milk yield, 0.556 and 13.827 for the fat percentage and 0.643 and 6.787 for the protein percentage.